IMPROVE PERFORMANCE THROUGH SATISFACTION AND PSYCHOLOGICAL EMPOWERMENT - Sulistiyani Sulistiyani; Roh Prihati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
This study aimed to analyze influence of psychological empowerment, effort and satisfaction on performance. In addition, this study also aims to analyze the influence of mediating variables of satisfaction relationship between psychological empowerment and effort on performance. Population and samples taken from doormat maker who are members of the UD. Anugrah 2017 for about 700 people . Samples taken from 106 maker/supplier. Data collection’s methods used by questionnaires. The analytic technique used is regression analysis with Path Analysis. The results showed that : 1). Psychological empowerment effect positive and significant satisfaction. 2). Effort have an positive effect and significant satisfaction. 3). satisfaction have an positive effect and significant on performance. 4). Psychological empowerment have an positive effect and significant on performance. 5). Effort have an positive effect and significant on performance.